Research on circuit breaker failure protection and the secondary accelerated fault isolation scheme of VSC-HVDC grids - Li, Andi; Li, Botong; Wen, Weijie; Li, Bin; Chen, Xiaolong (Frontiers in Energy Research, 2023)
When the direct current circuit breaker (DCCB) fails to operate, the fault range will further expand, endangering the safe operation of the power gird. Therefore, this study proposes a DCCB failure protection method and a secondary accelerated fault isolation scheme of voltage source converter-based high-voltage direct current (VSC-HVDC) grids. On the basis of considering the influence of DCCB disconnection, characteristics of fault current after the failure of the DCCB are analyzed, and a circuit breaker failure protection method based on “increase current” discrimination is proposed. By analyzing the logical relationship among failed breaker re-tripping, adjacent DCCB action, blocking of the converter station, and AC circuit breaker action, a secondary accelerated fault isolation scheme is proposed to minimize the fault isolation area. The scheme achieves the accelerated isolation of DC faults after the failure of the DCCB and avoids the trip of the AC circuit breaker effectively. Simulation results verify the effectiveness of the proposed scheme.